Organizing a party democracy: brazilian party organizations and elections in comparative perspective - Locatelli, Luís Gustavo Bruno (2024)
This thesis examines party organizational change at the cross-national and Brazilian levels through three independent articles. The first article examines how proportional representation (PR) systems and party structures influence party-group linkages, with a particular focus on candidate-centered systems. Analyzing data from 617 parties in 48 countries (1989-2019), we find a negative association between candidate-centered systems and party-group linkages, especially in weakly structured organizations. The second article examines the influence of local party organization types (established vs. appointed) on the electoral volatility of federal deputies in Brazilian municipalities (2010-2018). By influencing local career prospects, more decentralized and inclusive local party organizations (established party branches) facilitate local elite mobilization. This, in turn, leads to party vote stability (volatility) during elections. We test this hypothesis by combining a multi-method (DiD and survey experiment) and multi-level (organizations and individuals) approach. Finally, the third article argues that local Brazilian party-building efforts are influenced by mayoral elections, extending Duverger's basic proposition to the organizational level (2010 to 2020). Based on a panel analysis, we show that the "reduction effect" of single-member district plurality rule in mayoral elections limits local party institutionalization. As a result, this system discourages investment in local units beyond the "Duvergerian equilibrium (M+1)," suggesting that parties avoid investing in established local branches in municipalities with no prospect of winning local elections.